"Abomination to Egyptians" in Genesis 43 : 32, 46 : 34, and Exodus 8 : 22 - Pinker, Aron (Old Testament essays, 2009)
Available explanations of the causes for Egyptian sense of abomination in Genesis 43:32, 46:34, and Exodus 8:22 are either too general or incorrect. It is suggested that in Genesis 43:32 the sense of abomination possibly stems from the malodorous woolen garments worn by the Hebrews; in Genesis 46:34 it is perhaps a combination of basic farmer / shepherd distaste and hatred stemming from an association of shepherds with the barbaric nomadic chieftains on Egypt's north-eastern border ; and in Exodus 8:22 it might be driven by the Hebrews' custom of burning portions of animals sacrificed to a deity. These suggestions, while speculative, have a Sitz im Leben context.